KETERKAITAN TEKNIK BUDIDAYA MANGGA DENGAN PENDAPATAN PETANI (SUATU KASUS PADA PETANI MANGGA MAJALENGKA DAN CIREBON) - Rasmikayati, Elly; Suminartika, Eti; Saefudin, Bobby Rachmat (Fakultas Pertanian, Universitas Janabadra, 2024)
West Java is one of the provinces that has potential for mango cultivation because it has a climate that is suitable for this plant. However, in 2023 there will be a decline in mango production, followed by an increase in the level of mango consumption in Indonesia, which is indicated to be influenced by the way farmers cultivate mango plants. The aim of this research is to identify farmer characteristics and relate mango cultivation techniques to farmer income in two mango production centers in West Java, namely Majalengka and Cirebon. The research method used is descriptive statistics and non-parametric tests. Respondent selection used a two-stage stratified sampling technique. The sample for this research was 258 mango farmers in Majalengka and Cirebon. The research results show that the majority of mango farmers in Majalengka and Cirebon have a productive age range of 45 - 60 years with an elementary school education level and their main job is as mango farmers. Meanwhile, judging from the cultivation techniques, the majority of mango farmers in Majalengka and Cirebon plant mangoes in gardens/fields with the majority of farmers in Majalengka implementing a polyculture planting pattern, while Cirebon is more dominant in implementing a monoculture planting pattern with the gedong gincu variety as the main variety. Then, the majority of mango farmers in Majalengka and Cirebon have implemented off season technology in their mango cultivation activities. Mango farmers who have a risk-averse nature carry out harvesting independently and control pests. The majority of mango farmers use pesticides as a means of controlling pests. Then, there is a significant relationship between planting location, use of off season technology, and pest control and farmer income in Majalengka and Cirebon.Key-words: Mango cultivation techniques, farmer income, planting location, off season technology, pest control.